(untitled) (Research, Society and Development, 2021)
The need to reflect on the health care that has been offered in health facilities to the public in question, especially in relation to the nurse’s duties in caring for the elderly in the finiteness of life. The study aimed to reveal the role of nurses in caring for elderly people in the finiteness of life. It is an Integrative Literature Review, with a qualitative approach, carried out with the VHL, accessing the LILACS and BDENF databases. The selection of articles took place from September to October 2021. Studies published in full, in Portuguese and English, from 2015 to 2021 were included. Data collection was performed using a form, previously validated and adapted from Ursi (2005). The search resulted in 1,391 articles, being selected, after applying the inclusion and exclusion criteria, 13 articles. It was pointed out that nurses who offer palliative care work with the aim of meeting the needs of patients who need symptom relief and psychosocial care needs along with support for their families, especially in palliative care. It was concluded that the role of nursing in patient care in palliative care is essential, not only in the control of symptoms and pain relief, but also in communication with the family, also highlighting its role in the multidisciplinary team, in which it is prioritized comprehensive care, encompassing biopsychosocial aspects in the search for a better quality of life and well-being for the patient/family.